Azoospermia with variable testicular histology after 7 months of treatment with a deslorelin implant in toms - Novotny, R; Vitasek, R; Bartoskova, A; Cizek, P; Prinosilova, P; Novakova, K (Theriogenology, 2015)
The main aim of the study was to assess whether the longer use of a GnRH-agonist implant (deslorelin 4.7 mg, Suprelorin) in toms would lead to the suppression of spermatogenesis comparable with histologic appearance in juvenile animals as was previously described in dogs. The other aims were to monitor the progression of the testes size decrease and development of azoospermia 5 to 7 months after treatment with a GnRH-agonist implant. In animals, 5, 6, and 7 months after GnRH-agonist implant insertion, variable histological appearance of germinal epithelium was found, when tubules with elongating spermatids, round spermatids, spermatocytes, and spermatogonia as the most developed germinal cells were found in each group of toms. In all male cats, 5, 6, and 7 months after implant insertion, testosterone concentrations and testes size significantly differed between the first and the last visit. All animals, except one tom castrated 5 months after implant insertion, developed complete azoospermia. However, in this tom, all spermatozoa were immotile. Treatment with the subcutaneous GnRH-agonist implant was well tolerated, and no treatment-related adverse effects were noted. These results reported the efficacy of 4.7-mg deslorelin implant (Suprelorin) during its 7 months of use. The complete azoospermia confirms its contraceptive effect. However, the histologic evaluation revealed a great individual variability in the degree of spermatogenic suppression. The question as to whether spermatogenesis in toms can be suppressed in all males to the level of spermatogonia/primary spermatocytes after prolonged exposure to deslorelin has yet to be answered.
Keywords: hormon uvolňující gonadotropiny; Animals; Semen collection; Histologic evaluation; triptorelin-pamoát; Contraceptive Agents, Male; Drug Implants; Testis; Contraception; testis; azoospermie; kontraceptiva mužská; motilita spermií; Testis size; Cats; Azoospermia; GnRH-agonist; antikoncepce; Male; implantované léky; Triptorelin Pamoate; Gonadotropin-Releasing Hormone; Male cat; Testosterone; Sperm Motility; zvířata; mužské pohlaví; kočky; Spermatogenesis; spermatogeneze